AI AS A CREATIVE PARTNER: HOW ARTIFICIAL INTELLIGENCE IMPACTS STUDENT CREATIVITY AND INNOVATION: CASE STUDY OF STUDENTS FROM LATVIA, UKRAINE AND SPAIN - Olga Verdenhofa; Remigijus Kinderis; Galina Berjozkina (Baltic Journal of Economic Studies)
This study explores students' perceptions of Artificial Intelligence (AI) in the educational process, focusing specifically on creativity and confidence. As AI technology becomes increasingly integrated into higher education, understanding its impact on students' creative development and their confidence in using AI tools is crucial for shaping effective educational practices. To this end, a comprehensive questionnaire was designed and distributed to higher education students across Latvia, Ukraine, and Spain, resulting in a diverse sample of 89 respondents. The survey collected data on demographic information, general AI usage in education, and students' attitudes towards AI's impact on creativity. To analyse the data, the Kruskal-Wallis test was employed to examine country-based differences in AI usage frequency. The results showed no significant variance (p = 0.448). This finding led to the rejection of the hypothesis that students from EU countries use AI more frequently than those from non-EU countries. Descriptive data analysis revealed that 83% of students felt AI did not limit their creative expression, and 69% reported a positive impact on their ability to generate creative solutions. However, only 47% of students expressed confidence in using AI collaboratively, indicating mixed perceptions about its role in group creative tasks. These results suggest that while students generally view AI as supportive of their creativity, there is a need for increased efforts to enhance confidence in AI's collaborative and creative applications. In light of the escalating significance of AI in educational settings, this study is pivotal in elucidating the optimal integration of AI to nurture students' creative growth and fortify their confidence in the effective utilisation of AI tools. This research makes a significant contribution to the field by offering valuable insights into the evolving role of AI in higher education, emphasising the importance of balanced integration strategies for maximising its potential in the educational sphere.